A novel mechanism for exhaust steam waste heat recovery in combined heat and power unit. (15th October 2017) - Zhao, Shifei; Ge, Zhihua; He, Jie; Wang, Chunlan; Yang, Yongping; Li, Peifeng
Graphical abstract: Schematic of the exhaust steam recovery in coal-fired CHP unit. Highlights: A novel mechanism for exhaust steam waste heat recovery is proposed. Pinch analysis and Sankey diagrams are used in the thermodynamic analysis. The sensitivity analysis is performed and evaluated with several metrics. The feasibility and techno-economic evaluation are considered. Abstract: Combined heat and power (CHP) has been identified as an important approach for fossil fuel utilization with high efficiency and pollutant concentration control. In this study, an optimized process for in-depth exhaust steam utilization was proposed to further exploit the energy saving potential of CHP unit. In the novel system, the utilization of the exhaust steam was combined with the heating process for air and condensate water, largely recovering the waste heat and leading to an improvement in the performance of the CHP unit. EBSILON Professional was used to build the model; and compared with the reference system, thermodynamic analysis and techno-economic evaluation were conducted to reveal the characteristics of the novel system. The results showed that, in the design condition, the exhaust steam utilization ratio in the novel system had a significant increment of 22.74% than that in the reference system, leading to a sharp increase of 16.26% in heating capacity and 0.83 MW in net electricity output, bringing about 5.06% improvement in net generating efficiency. Meanwhile, the net annual revenues of the novel system can reach 1.80 million USD.